2021
DOI: 10.1038/s41467-021-22210-3
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in severe COVID-19 induces a TGF-β-dominated chronic immune response that does not target itself

Abstract: The pathogenesis of severe COVID-19 reflects an inefficient immune reaction to SARS-CoV-2. Here we analyze, at the single cell level, plasmablasts egressed into the blood to study the dynamics of adaptive immune response in COVID-19 patients requiring intensive care. Before seroconversion in response to SARS-CoV-2 spike protein, peripheral plasmablasts display a type 1 interferon-induced gene expression signature; however, following seroconversion, plasmablasts lose this signature, express instead gene signatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
148
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 183 publications
(182 citation statements)
references
References 61 publications
20
148
0
Order By: Relevance
“…Regarding the humoral immunity to SARS-CoV-2, several studies demonstrated an extraordinary B cell response with absence of germline centers in deceased COVID-19 patients, appearance of extra-follicular B cell activation together with neutralizing antibodies, an extensive class switching to IgG and IgA accompanied by limited somatic hypermutation, as well as TGF-β instructed SARS-CoV-2 unspecific B cell responses (24)(25)(26)(27). As others have previously shown (6), we observed a significant expansion of plasmablasts in severe COVID-19 patients accompanied by IgA and IgG SARS-CoV-2-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the humoral immunity to SARS-CoV-2, several studies demonstrated an extraordinary B cell response with absence of germline centers in deceased COVID-19 patients, appearance of extra-follicular B cell activation together with neutralizing antibodies, an extensive class switching to IgG and IgA accompanied by limited somatic hypermutation, as well as TGF-β instructed SARS-CoV-2 unspecific B cell responses (24)(25)(26)(27). As others have previously shown (6), we observed a significant expansion of plasmablasts in severe COVID-19 patients accompanied by IgA and IgG SARS-CoV-2-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Systemically distributed antibodies (mainly IgG, IgM, and IgA1) curtail virus propagation after productive infection of the host, while the presence of antigenspecific antibodies secreted at the mucosal surfaces (IgA2, IgA1, and IgM) may prevent initial infection of the host [7]. The absence of IgA2 antibodies specific for SARS-CoV-2 antigens in severely diseased COVID-19 patients has also been demonstrated [8], suggesting that mucosal anti-viral IgA antibodies may protect the host from a severe course of COVID-19. Several studies have reported the presence of RBD-binding antibodies in unexposed healthy individuals [9,10,11,12,13].…”
Section: Main Textmentioning
confidence: 97%
“…Furthermore, activation of PPAR-γ signaling via rosiglitazone (a potent PPAR-γ agonist) treatment antagonized TGF-β-mediated myofibroblast differentiation likely by reinforcing the lipogenic phenotype ( El Agha et al, 2017b ). Interestingly, TGF-β upregulation has been found to be induced by SARS-Cov-2 infection ( Agrati et al, 2020 ; Chen, 2020 ; Ferreira-Gomes et al, 2021 ) and associated with several complications of severe COVID19, such as ARDS and pulmonary fibrosis. Thus, it is plausible that FGF10, likely via PPAR-γ activation, gets involved in an attempt to replenish LIFs lost to unrestrained MYF differentiation – driven by TGF-β upregulation and chronic epithelial injury ( Figure 2B ).…”
Section: Fgf10 In the Lif To Myf Switch During Fibrosis Formation And Resolutionmentioning
confidence: 99%